(untitled) (Global Journal of Management and Business Research, 2020)
Performance Management System (PMS) is often used by managers to align the goals of the organization to the goals of their employees, and ensure productivity and efficiency. PMS has always been a crucial function of human resource management. However recent studies have shown that in the long term, the traditional system of performance management damages morale, motivation, teamwork, and stunts creativity and contribution. As a result, companies are doing away with the old ways of performance reviews and are opting for more flexible and efficient processes. This study aims at understanding the deficiencies in the old system and the reasons for adopting more relevant and upcoming trends in the field of performance management.